2015
DOI: 10.1590/s1517-838246246220131143
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of prodigiosin by Serratia marcescens MO-1 using ram horn peptone

Abstract: This work addresses the production of prodigiosin from ram horn peptone (RHP) using MO-1, a local isolate in submerged culture. First, a novel gram-negative and rod-shaped bacterial strain, MO-1, was isolated from the body of the grasshopper (Poecilemon tauricola Ramme 1951), which was collected from pesticide-contaminated fields. Sequence analysis of 16S rDNA classified the microbe as Serratia marcescens. The substrate utilization potential (BIOLOG) and fatty acid methyl ester profile (FAME) of S. marcescens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 32 publications
4
35
0
9
Order By: Relevance
“…Subsequent increase either did not affect or caused adverse effect on responses. Especially for CFP, concentration greater than 9 g/L was inhibitory to rhamnolipid production which might be due to high salt concentration, some toxic materials, and the change of C/N ratio of culture medium (Kurbanoglu et al 2015). The elliptical shape of the contour plots indicates a significant interaction, while circular shape indicates insignificant interaction (Gurkok et al 2011).…”
Section: Selection Of Optimal Carbon and Nitrogen Sourcesmentioning
confidence: 98%
“…Subsequent increase either did not affect or caused adverse effect on responses. Especially for CFP, concentration greater than 9 g/L was inhibitory to rhamnolipid production which might be due to high salt concentration, some toxic materials, and the change of C/N ratio of culture medium (Kurbanoglu et al 2015). The elliptical shape of the contour plots indicates a significant interaction, while circular shape indicates insignificant interaction (Gurkok et al 2011).…”
Section: Selection Of Optimal Carbon and Nitrogen Sourcesmentioning
confidence: 98%
“…This positive effect of CFP may be a result of high amino acid and mineral contents [20,23]. The nitrogen contents of CFP, BP, TP and YE are 9.0 [23], 13.8, 10, and 10.9 (g/100 g) [26], respectively. Since CFP is chemically synthesized, the ash content (about 41%) is also high in other organic nitrogen sources (11-15%) [23].…”
Section: Effect Of Organic Nitrogen Sources On Production Of Xanthanmentioning
confidence: 98%
“…It was found that applications higher than 4 g/L CFP had a negative effect for xanthan concentration. This negative effect may be a result of high nitrogen source and salt concentration [21,26]. It can be said that the addition of 4 g/L CFP to the CM may provide the proper carbon/nitrogen (C/N) ratio for xanthan gum production.…”
Section: Effect Of Cfp On Xanthan Gum Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of Fatty Acid Methyl Esters (FAMEs) from whole cell fatty acids of bacterial isolates were carried out using GC according to the method described by the Kurbanoglu et al [10]. B. cereus strains were grown and maintained on Nutrient Agar (NA; Merck) slants at 28 °C and 4 °C, respectively.…”
Section: Isolation and Identification Of Microorganismsmentioning
confidence: 99%